PENERAPAN KETERAMPILAN MENULIS TEKS BERITA BERBASIS TEKNIK STUDI WISATA KELAS VIIB SMP PLUS AL-FALAH AL-MAKKY MALANG - Muhammad Ali Ridho Syam; Hosniyeh Hosniyeh (Lingua Franca:Jurnal Bahasa, Sastra, dan Pengajarannya, 2025)
This study aims to improve students' skills in writing news texts through the application of the study tour technique in Class VII B of SMP Plus Al-Falah Al-Makky Gondanglegi, Malang. This research is a Classroom Action Research (CAR) conducted in two cycles, each consisting of planning, implementation, observation, and reflection stages. The study tour technique was implemented by inviting students to directly observe various activities within the school and Islamic boarding school environment, such as flag ceremonies, sanitation programs, and daily student routines. The observations served as the basis for writing news texts in accordance with proper structure and language conventions. Data were collected through observation, interviews, and documentation, and assessed based on five aspects: originality of ideas, engaging headlines, news text structure, language usage, and paragraph coherence. The results showed a significant improvement in students' writing abilities. In the pre-cycle stage, the average student score was 58.68, with only 3 students (7.89%) meeting the Minimum Competency Criteria (KKM). After the first cycle, the average score increased to 67.5 with 15 students (39.47%) achieving KKM. In the second cycle, the average rose to 79.16 with 25 students (65.79%) achieving KKM. These findings indicate that the study tour technique is effective in enhancing students' news writing skills in a contextual and meaningful way.